Democracy In Islamic Politics (Historical Review of the Election of the Head of State in Islam) - Munawaroh, Hifdhotul; Nurjanah, Nurjanah; Diana, Rashda (Jurnal Kawakib, 2024)
Muslim scholars are still debating democracy in Islam. Some of them reject democracy because the essence of democracy is the sovereignty of the people. At the same time, siyasah syar'iyyah (Islamic politics) is the sovereignty of Allah with its various provisions. Others argue that some of the substances of democracy are the same as the essence of Islamic politics, which have existed before democracy itself began to be hot in the discussions of political experts today. One form of democracy is the election of leaders. In the history of Islam, the appointment of leaders can be made in several ways, namely through nash (holy books), deliberation of ahlul halli wal 'aqd, wilayah al 'ahd, and coercion. The method of selecting leaders was implemented in the election and appointment of Khulafa ar Rasyidun as Caliph.